Mercury concentrations in Atlantic bottlenose dolphins (Tursiops truncatus) inhabiting the Indian River Lagoon, Florida: Patterns of spatial and temporal distribution. Issue 1 (15th August 2015) - Schaefer, Adam M.; Titcomb, Elizabeth Murdoch; Fair, Patricia A.; Stavros, Hui-Chen W.; Mazzoil, Marilyn; Bossart, Gregory D.; Reif, John S.
Highlights: Samples between 2003 and 2012 showed a significant linear decrease over time ( p  = 0.04). Significant differences in spatial distribution of THg in resident IRL dolphins observed. Temporal and spatial pattern analysis of exposure to THg in this sentinel species may have implications for both ecosystem and regional public health. Abstract: Bottlenose dolphins ( Tursiops truncatus ) inhabiting the Indian River Lagoon, FL (IRL) have tissue mercury concentrations among the highest reported worldwide. Analysis of total mercury (THg) concentrations in blood collected between 2003 and 2012 showed a significant linear decrease over time ( p  = 0.04). Significant differences in the spatial distribution of THg in resident IRL dolphins were also observed with a general gradient in concentration from north to south. Evaluation of local biogeochemistry and accumulation of mercury in prey species is needed to better understand factors influencing the distribution of Hg in the apex predator. Analyses of temporal and spatial patterns of exposure to THg in this sentinel species may have implications for both ecosystem and public health in the region.